Three new species of Kudinopasternakia Guţu, 1991 (Crustacea: Tanaidacea: Sphyrapodidae) from Brazilian waters - Santos, Kátia Christol Dos (Zootaxa, 2007)
Three new species of sphyrapodid tanaidaceans, Kudinopasternakia amazonica, K. brasiliensis and K. trispinosa, are described and illustrated from benthic samples taken at 230–700m depth off Northern and Southeast Brazil. The main characters used for the separation of the species are rostral shape, pleonite epimera, the number of cuspidate setae on the carpus and propodus of pereopod 1 and the presence or absence of a thick distodorsal seta on propodus of pereopod 4. Exopods were observed on pereopods 4 and 5 of the mancas on two of new species. A key to the genus Kudinopasternakia is presented.